Rasch Calibration and Differential Item Functioning (DIF) Analysis of the School Well-Being Scale for Students - Hermansyah, Eka; Rizkyanti, Charyna Ayu; Hakim, Lukman Nul (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to examine the quality of the school well-being scale for high school students..This study used a quantitative approach with Rasch model analysis. The validity, reliability, and differential item functioning (DIF) assessment are all part of the psychometric examination. The 165 high school students in Mataram, West Nusa Tenggara province who took part in this research were 40 males and 125 girls, ages 11 to 18 (mean age = 15.87, SD = 1.39). The findings of the Rasch analysis show the instrument passes the validity test but has weak reliability. The statistical analysis of the Cronbach alpha reliability coefficient of the instrument is 0.43. More detailed results are shown by the Rasch model analysis reliability of person on 0.47 and item reliability of 0.98. This result explains the good quality of the instrument, while the reliability of the instrument needs to be strengthened by controlling the demographic factors. The scale can be used by school management to understand well-being of the students, and further for the improvement of school quality.